The Effect of Fish Production and Environmental Factors on Phytoplankton in Hypertrophic Fishponds - Radojičić, Marija; Kopp, Radovan; Müllerová, Barbora; Šorf, Michal (Mendelova univerzita v Brně, 2022)
Fishponds form substantial part of standing water ecosystems in the landscape of the Central Europe. We studied the effects of fish production and environmental parameters on phytoplankton in fifteen fishponds of various size, fish production and situated at different altitudes. Water and plankton samples were collected from April to October 2018 and 2019. Phytoplankton abundance, zooplankton biovolume, total phosphorus, total nitrogen, ammonia-nitrogen, nitrites, nitrates, phosphates, and total iron concentration were determined. Based on average values of total nitrogen (8.53 mg.l-1), total phosphorus (0.399 mg.l-1), and chl-a (180 µg.l-1) all fishponds were classified as hypertrophic. Fish production was significantly correlated only with altitude. With increasing altitude, fishponds have a lower nutrient content, lower temperature, and hence lower production. The direct effect of fish production on phytoplankton was not observed. Two environmental parameters significantly explained the variability in phytoplankton - altitude and total iron concentration. Our results indicate that besides traditionally monitored parameters like nitrogen and phosphorus concentration, the attention should also be focused on other factors potentially affecting studied ecosystems, hypertrophic fishponds.
Keywords: phytoplankton; altitude; iron concentration; fishpond; fish production